TiO2-rGO Composite for Photocatalytic Decolorization of Methylene Blue Under the Visible Light Illumination - Hidayati, Ulfa Farizka; Aritonang, Anthoni B.; Destiarti, Lia (BERKALA SAINSTEK, 2021)
Titanium dioxide-reduced graphene oxide (TiO2-rGO) was synthesized by hydrothermal method using TiO2 powder and rGO precursor from graphite rod by modified Marcano Method. The obtained TiO2-rGO photocatalyst was characterized by X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), and Diffuse reflectance UV (DRUV). Based on XRD diffractogram, it is known that TiO2 has an anatase crystal phase. In the FTIR spectrum, it was observed that there was an absorption peak at the wavenumber of 1630 cm-1 from the vibration (C=C) as an indication that the C atom was incorporated into the TiO2 structure. The incorporation of C atoms into the TiO2 structure to form TiO2-rGO causes the bandgap energy to decrease from 3.29 eV to 3.20 eV. The photocatalytic activity was tested against decolorization of methylene blue solution for 180 minutes under visible light illumination from a 50 watt LED lamp. Every 10 minutes, absorbance was measured using a UV-Vis spectrophotometer at a wavelength of 664 nm. TiO2-rGO photocatalyst has better photocatalytic activity with %D of 96.39% under UV light and 84.32% under visible light illumination, while TiO2 is only able to degrade 93.87% and 36.55%, respectively.